(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2024)
Ljiljana Đurđić is considered an important Serbian women writer. Her oeuvre is not large, although significant, and even besides that, it is symptomatic that in the scientific community this significance is not recognized. Ljiljana Đurđić was a poetess, then a prosaist and a columnist. From the perspective of feminist, contextual and poetic analysis of prose, I am showing how this female author in her writings, in her editorial policy in the journal ProFemina, but foremost in her prose advocated for the modernist paradigm. This is interesting in the context of Serbian literary culture of the 20th century which was constituted through the struggle of modernist and antimodernist poetics. The literary work of this author I place in Belgrade’s socialist modernist culture which molded her and which she had never abandoned. Many of her beliefs about the dynamics of global (worldly) and local Serbian literary culture she expressed in the introduction to the Anthology Women’s Continent: Anthology of Contemporary Serbian Women’s Story, which she edited. Even though she wrote about female prose writers that are included in it, that text functions as her program text. In the analysis of several stories, I pointed out how the modernist literary paradigm is embodied in the narrative. I singled out the following aspects: self-referentiality and cosmopolitanism. In the text, I present the thesis that feminist theories, which from the nineties of the 20th century became an important constitutive force in the political, cultural and economic transformations of Serbian society in the conditions of war’s transition, substantially influenced Ljiljana Đurđić’s actions in the public sphere, and above all, in literature. At the bases of her actions are contradictory beliefs, that are typical for a culture in which she was forming and working. I singled out two constitutive contradictions, the attitude towards theory and towards feminism. She had a negative attitude towards theory, but at the same time, she read it and occasionally called upon it: theory functioned as a literary work to the extent that is indispensable today. The attitude towards feminism was changing. During socialism in the literary culture of the dominant stream, to which Ljiljana Đurić belonged, the influence of feminism was not that important. Socialist literature of the dominant steam constituted in opposition to feminism. When feminism from the beginning of the nineties started to globalize and became significant, Ljiljana Đurđić entered into feminist theories and used them to articulate her own actions. After 2000, feminism lost its significance, and Ljiljana Đurđić expressed a typical post-feminist belief that feminism had been overcome and was no longer needed. Nevertheless, her entire work as well as her prose can best be understood from the perspective of feminist beliefs and ideologies.